2020
DOI: 10.1108/aia-12-2019-0049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sleep disturbances, gastrointestinal problems and eating behaviors in Turkish children with autistic disorder and PDD-NOS

Abstract: Purpose The purpose of this study is to evaluate the relationship between sleep disturbances, gastrointestinal (GI) problems and eating behaviors in children who are diagnosed with autistic disorder (AD) and pervasive developmental disorder not otherwise specified (PDD-NOS). Design/methodology/approach This study was conducted with 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Studies showed less sleep disorders in the PDD-NOS-group ( 33 , 93 , 94 ) but another did not ( 35 ) ( Table 4 ). Feeding disorders were less common in the PDD-NOS group than in the AD group ( 35 , 93 , 94 ). However, one study did not confirm this result ( 85 ) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 96%
“…Studies showed less sleep disorders in the PDD-NOS-group ( 33 , 93 , 94 ) but another did not ( 35 ) ( Table 4 ). Feeding disorders were less common in the PDD-NOS group than in the AD group ( 35 , 93 , 94 ). However, one study did not confirm this result ( 85 ) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 96%
“…Twelve articles ( 19 , 21 , 22 , 24 , 25 , 32 , 34 37 , 39 , 41 ) recorded cases of children with ASD complaining of simple abdominal pain. Seven studies ( 18 , 18 , 20 , 23 , 29 , 30 , 38 ) reported cases of defecation-related abdominal pain, and two ( 26 , 28 ) found no abdominal pain. Seven studies ( 18 19 , 21 , 23 , 26 , 41 ) compared abdominal pain in ASD and corresponding TD controls, with an OR of 2.60 (95% CI: 2.07, 3.26).…”
Section: Resultsmentioning
confidence: 99%